2014
DOI: 10.1105/tpc.113.121731
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis DELLA and JAZ Proteins Bind the WD-Repeat/bHLH/MYB Complex to Modulate Gibberellin and Jasmonate Signaling Synergy  

Abstract: Integration of diverse environmental and endogenous signals to coordinately regulate growth, development, and defense is essential for plants to survive in their natural habitat. The hormonal signals gibberellin (GA) and jasmonate (JA) antagonistically and synergistically regulate diverse aspects of plant growth, development, and defense. GA and JA synergistically induce initiation of trichomes, which assist seed dispersal and act as barriers to protect plants against insect attack, pathogen infection, excessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
166
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(167 citation statements)
references
References 112 publications
1
166
0
Order By: Relevance
“…For example, GLABRA1, PHYTOCHROME INTERACTING FACTORs, MYC2, GLABRA3, ENHANCER OF GLABRA3, Class I TCP, BRASSINAZOLE-RESISTANT1, ETHYLENE INSENSITIVE3, AUXIN RESPONSE FACTOR6, and SPLs, were reported as targets of DELLA proteins to regulate diverse aspects of GA-mediated processes (Yu et al, 2012;Davière et al, 2008Davière et al, , 2014Davière et al, , 2016de Lucas et al, 2008;Feng et al, 2008;Hong et al, 2012;Wild et al, 2012;Qi et al, 2014;Bai et al, 2012;An et al, 2012;Oh et al, 2014). Furthermore, our study and Xu et al (2016) found that the B-box protein CO also interacts with DELLA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GLABRA1, PHYTOCHROME INTERACTING FACTORs, MYC2, GLABRA3, ENHANCER OF GLABRA3, Class I TCP, BRASSINAZOLE-RESISTANT1, ETHYLENE INSENSITIVE3, AUXIN RESPONSE FACTOR6, and SPLs, were reported as targets of DELLA proteins to regulate diverse aspects of GA-mediated processes (Yu et al, 2012;Davière et al, 2008Davière et al, , 2014Davière et al, , 2016de Lucas et al, 2008;Feng et al, 2008;Hong et al, 2012;Wild et al, 2012;Qi et al, 2014;Bai et al, 2012;An et al, 2012;Oh et al, 2014). Furthermore, our study and Xu et al (2016) found that the B-box protein CO also interacts with DELLA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The JA receptor JASMONIC ACID IN-SENSITIVE1, the tomato ortholog of the ubiquitin ligase CORONATINE INSENSITIVE1 in Arabidopsis, is involved in this JA-mediated signaling cascade (Li et al, 2004;Katsir et al, 2008;Kang et al, 2010;Bosch et al, 2014). It remains to be investigated whether a synergistic effect between GA and JA signaling, similar to that observed in Arabidopsis (Qi et al, 2014), also promotes glandular trichome development. The development of multicellular glandular trichomes proceeds through the enlargement of single epidermal cells, followed by several cell divisions to generate a structure perpendicular to the epidermal surface (Fig.…”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%
“…Within this complex, the bHLH factor (such as GL3) interacts with the MYB factors (MYB75 or GL1) via their N-terminal domains, while JAZ repressors competitively interact with the N-terminal domains of these bHLH and MYB factors to disrupt and repress the WD-repeat/bHLH/MYB complex essential for JA-regulated anthocyanin biosynthesis and trichome initiation (Qi et al, , 2014. JA induces the degradation of JAZs to release this WD-repeat/bHLH/MYB complex, which further activates the expression of the downstream genes to enhance anthocyanin biosynthesis and trigger trichome initiation .…”
Section: Myb24mentioning
confidence: 99%